2011
DOI: 10.1007/s12892-010-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hybrid performance based on the genetic distance of parental lines in two-line rice (Oryza sativa L.) hybrids

Abstract: A total of six TGMS (thermosensitive genic male sterile lines) and nine pollinator lines were subjected to molecular characterization using 48 genome-wide SSR (simple sequence repeat) markers. Cluster analysis revealed clear differentiation among the TGMS lines according to their source of origin. The SSR-based genetic distance between the hybrids of the parental lines ranged from 0.36 to 0.79 suggesting a high degree of genetic divergence. Among a set of 54 hybrids generated using parental lines, 32 showed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The genetic diversity estimates based on molecular markers are helpful in assigning germplasm into heterotic groups and in assessing pedigree relationship among germplasm (Melchinger and Gumber 1998), but with very limited value in predicting hybrid yield performance as evidenced in hybrid maize (Marsan et al 1998;Balestre et al 2008;Legesse et al 2008) and hybrid rice (Zhang et al 1995;Zhao et al 1999;Xu et al 2002;Singh et al 2011). With insufficient knowledge of association of functional molecular markers and yield, the information derived from molecular markers currently is limited to the use of assigning parents into germplasm group or heterotic groups, and to provide a general guideline of avoiding heterotic groups from mixture during parent breeding.…”
Section: Heterotic Groups Based On Markersmentioning
confidence: 99%
“…The genetic diversity estimates based on molecular markers are helpful in assigning germplasm into heterotic groups and in assessing pedigree relationship among germplasm (Melchinger and Gumber 1998), but with very limited value in predicting hybrid yield performance as evidenced in hybrid maize (Marsan et al 1998;Balestre et al 2008;Legesse et al 2008) and hybrid rice (Zhang et al 1995;Zhao et al 1999;Xu et al 2002;Singh et al 2011). With insufficient knowledge of association of functional molecular markers and yield, the information derived from molecular markers currently is limited to the use of assigning parents into germplasm group or heterotic groups, and to provide a general guideline of avoiding heterotic groups from mixture during parent breeding.…”
Section: Heterotic Groups Based On Markersmentioning
confidence: 99%
“…In the two‐line system, male‐sterility is controlled by one or more pairs of recessive nuclear genes that determine hyper‐sensitivity to environmental conditions, with resulting male sterility. Photosensitive (PGMS) and thermosensitive (TGMS) genetic male sterile lines (referred to as S‐lines) have been developed in China (Lu et al., ) and other countries (Virmani et al., ; Singh et al., ). The two‐line system has a number of advantages over the three‐line system: Maintainer lines are not needed in the two‐line system as the PGMS and TGMS respond to ambient light and temperature regimes, respectively; therefore, by altering light or temperature, the degree of male sterility can be controlled so that seed of the S‐line can be readily produced.…”
Section: Hybrid Ricementioning
confidence: 99%
“…The predominance of WA-CMS progeny, suggests that there may currently be a high regional susceptibility of rice to S. furcifera in China and North Vietnam (hypothesis B6). It is commonly held that increased genetic distance between parents results in an improved yield of hybrids (Zhang et al, 1995;Xiao et al, 1996;Xu et al, 2002;Singh et al, 2011), although there may be some threshold above which it becomes difficult to achieve successful restoration of fertility. Several breeding programs have attempted to increase the diversity of their parental lines and optimize the genetic distance between male-sterile and restorer parents (Peng et al, 1999;Singh et al, 2011).…”
Section: Is Hybrid Rice More Susceptible To Insect Damage?mentioning
confidence: 99%
“…However, studies conducted in plants showed inconsistent results. For example, genetic distance was not correlated with heterosis for rice hybrid seed yield (Teklewold and Becker, 2006) and was negatively correlated with heterosis of yield (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 96%